An overview of the pathfinder clinical trials program: Long‐term efficacy and safety of N8‐GP in patients with hemophilia A. (17th September 2020) - Matsushita, Tadashi; Mangles, Sarah
Abstract: N8‐GP (turoctocog alfa pegol, Esperoct ® ; Novo Nordisk A/S, Bagsvaerd, Denmark) is a state‐of‐the‐art, extended half‐life factor VIII (FVIII) molecule used for prophylactic and on‐demand treatment of patients with hemophilia A. The pathfinder clinical trial program, which began with the pathfinder1 trial in 2010, was developed to assess the long‐term efficacy and safety of N8‐GP in children, adolescents, and adults. The pivotal pathfinder2 (adolescents and adults) and pathfinder5 (children) trials were completed in late 2018, and comprehensive analyses of the end‐of‐trial results are published together with this article as part of an N8‐GP Supplement. Furthermore, results from the pathfinder3 trial, which was designed to evaluate the safety and efficacy of N8‐GP during major surgery, have also recently been finalized. Here, we provide an overview of the pathfinder clinical development program and summarize key data from the completed pathfinder trials. We also provide perspectives on the future of extended half‐life FVIII molecules in the treatment of patients with hemophilia A and describe currently ongoing pathfinder trials.